1933
DOI: 10.1085/jgp.16.5.767
|View full text |Cite
|
Sign up to set email alerts
|

The Digestion and Inactivation of Maltase by Trypsin and the Specificity of Maltases

Abstract: In 1925 Leibowitz (1) proposed the theory that there are two kinds of maltases,--one kind present in yeast, having the power of hydrolyzing maltose and a-methylglucoside and another found in moulds (2--4) with only maltose-splitting power. Thus he would differentiate between glucosidomaltase and glucomaltase. But Weidenhagen (5) has taken quite a different view. He thinks that sucrose may be hydrolyzed by a-glucosidase and by a/~-h-fructosidase, and maltose only by a-glucosidase. This he explains by his steric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1934
1934
1954
1954

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It has also been shown by Tauber and Kleiner (82) that maltase is readily digested by trypsin. Tauber (78) found emulsin to be indigestible by pepsin, trypsin, and pancreatin during several weeks incubation at 40°C.…”
Section: Digestion Of Enzymes By Proteasesmentioning
confidence: 80%
“…It has also been shown by Tauber and Kleiner (82) that maltase is readily digested by trypsin. Tauber (78) found emulsin to be indigestible by pepsin, trypsin, and pancreatin during several weeks incubation at 40°C.…”
Section: Digestion Of Enzymes By Proteasesmentioning
confidence: 80%
“…We found that sucrose was, in all except one of the subjects, metabolized at least as rapidly as glucose by the saliva. There is some disagreement in the literature concerning the existence of invertase in saliva (Bourquelot, 1910;Lisbonne, 1910;Tauber & Kleiner, 1933;Wohrinz, 1938;Volker, 1950). The fact remains, however, that unfiltered whole saliva can metabolize the disaccharides sucrose and maltose no less readily than glucose.…”
Section: Discussionmentioning
confidence: 99%